The Impact of Evaluation Methods on Students' Learning Achievement in Primary School Mathematics Education: A Mixed-Methods Study - Sihotang, Minora; Utari, Utari; Sihotang, Togarman (Jurnal Ilmu Pendidikan dan Humaniora, 2022)
In the realm of primary school mathematics education, the choice of evaluation methods holds a critical key to unlocking the potential of young learners. This mixed-methods research endeavors to illuminate the intricate relationship between assessment techniques and students' learning achievement. By integrating both quantitative and qualitative data, it offers a comprehensive understanding of the impact of different evaluation methods on students' experiences and outcomes in the realm of primary school mathematics. The quantitative phase of this study reveals compelling correlations between specific evaluation methods and students' learning achievement. Formative assessments, characterized by their immediate feedback and constructive nature, emerge as potent contributors to learning achievement. Students exposed to a higher frequency of formative assessments exhibit higher math test scores, revealing a strong positive correlation. The qualitative phase provides deeper insights into students' attitudes and experiences with various evaluation methods. Students express a strong preference for formative assessments, emphasizing the value of feedback and personal growth. Teachers underscore the importance of a balanced approach to assessment, combining different methods to address diverse learning styles and needs. Parents play a crucial role in supporting their children's education and express a range of expectations regarding assessment approaches. The research findings bear substantial implications for educational practices, policymaking, and curriculum development. Educators are encouraged to adopt a balanced approach that leverages the power of formative assessments while considering students' grade levels and socioeconomic backgrounds. Policymakers are positioned to develop evidence-based policies and standards that promote the use of effective assessment methods and equitable educational resources. In conclusion, this research unfolds a compelling narrative of the symbiotic relationship between evaluation methods and students' learning achievement in primary school mathematics education.